PERHITUNGAN KEKUATAN STRUKTUR GEDUNG PT. RODA INDOTRED MENGGUNAKAN ETABS - Satria; Darmadi; Tri Rahmat Utama (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2022)
The rapid development of buildings at this time is often not supported by good maintenance. This study aims to obtain data on the level of structural safety in the existing condition of the PT. Indotred Wheel. The assessment stages used are the initial assessment stage and the detailed assessment. The analysis stage is carried out on the condition of the strength of the structural components. The assessment process is carried out through field and laboratory testing. Field testing uses Ultrasonic Pulse Velocitymeter and Core Drill equipment to determine the compressive strength of concrete and a Rebar Locator/R-bar meter to determine the number and diameter of installed reinforcing steel. Testing in the laboratory for compressive testing of Core Concrete samples. Data analysis using ETABS v9.7.4 program. It is known that the slab structure used in this office building uses a conventional reinforced concrete floor slab with a thickness of 12 cm on Lt. 1 to 2 and using additional bondeck formwork on Lt. 3 to 4 with typical two-layer reinforcement 8- 150. Conventional reinforced concrete beam structure & steel profile. Based on the results of the capacity analysis of reinforced concrete & steel beams in accordance with the results of field investigations, that all elements of Lt. 1 to 4 the ratio of the moment or shear force 1.0. Column structural elements in this building use reinforced concrete and conventional steel. Based on the results of the analysis of reinforced concrete columns with PCA Column that the column capacity is able to withstand combined loads that occur in the building. The results of data calculations using ETABS and manuals are known that the structural elements of Columns, Beams and Plates are able to support combined loads according to their respective floor functions.